Nested Stromal Epithelial Tumor of the Liver in Beckwith-Wiedemann Syndrome. (July 2013) - Malowany, Janet I.; Merritt, Neil H.; Chan, Nancy G.; Ngan, Bo-Yee
Beckwith-Wiedemann syndrome (BWS) is an imprinting disorder characterized by overgrowth, congenital malformation, and tumor predisposition. Children with BWS have a higher incidence of tumors, commonly intra-abdominal tumors such as Wilms tumor, hepatoblastoma, and adrenal cortical carcinoma. Here, we describe the first case of a rare hepatic malignancy of nested stromal epithelial tumor (NSET) of the liver in a child with BWS. A 22-month old girl with BWS had a new incidental liver mass. Her alpha-fetoprotein levels were normal. She underwent a liver segmentectomy. Histopathologic features combined with immunohistochemistry results (positivity for pankeratin [AE1/3], CD56, CK19, CD117, CD99 [weak membranous pattern], β-catenin, and WT1-COOH [focal]), were diagnostic of NSET of the liver. This is the first case of NSET of the liver associated with BWS. Its occurrence at such an early age is consistent with the tumor predisposition of BWS.